3-Component synthesis of α-substituted sulfonamides via Brønsted acid-catalyzed C(sp3)–H bond functionalization of 2-alkylazaarenes. Issue 24 (12th February 2016) - Beisel, T.; Kirchner, J.; Kaehler, T.; Knauer, J.; Soltani, Y.; Manolikakes, G.
Abstract : A Brønsted acid-catalyzed addition of 2-alkylazaarenes to in situ generated N -sulfonylimines through selective C(sp 3 )–H bond functionalization has been developed. Abstract : A Brønsted acid-catalyzed addition of 2-alkylazaarenes to in situ generated N -sulfonylimines through selective C(sp 3 )–H bond functionalization has been developed. This protocol provides an atom- and step-economic approach to α-substituted sulfonamides.